Epstein-Barr Virus-Associated Acute Interstitial Nephritis - Luís, Telma (2022)
Epstein-Barr virus (EBV) infection is usually asymptomatic in childhood, but acute kidney injury (AKI) may be a rare complication during its course. We report a case of a 5-year-old female presented with fever, vomiting, abdominal pain, anorexia, anemia, thrombocytopenia and acute oliguric renal failure with titer-confirmed EBV infection. Renal biopsy specimen revealed an acute interstitial nephritis (AIN) and endocapillary glomerulonephritis with EBV inclusions in renal tubules epithelium. Methylprednisolone pulse therapy was performed, followed by oral corticoid therapy. Hemodialysis was required for 10 days with renal function complete recovery in 17 days. Physicians should be alert of uncommon presentations of EBV infection in children and consider this differential diagnosis when facing AKI.